(untitled) (Mustansiria Dental Journal, 2018)
Aim of this study was to evaluate the success of buccal sliding flap used in the reconstruction of oroantral defects, and clarify its indications and size limitations. In this prospective clinical study, buccal Sliding flap was used for closure of oroantral defect in 23 patients with different indications which included; 4 defects resulting from maxillary cysts (radicular and residual cyst) ,12 newly created medium size oroantral communications, 7 cases with chronic oroantral fistula. The defect diameter range between 3-8 mm. Patients were evaluated for signs of flap epithelialization, infection, and fistulae recurrence. The epithelialization process was completed in 19 patients after 2 weeks without any complication. However, partial dehiscence of the flap occurred in 4 patients with chronic oroantral fistula. The results of this series support the view that the use of buccal sliding flap is a simple, convenient, and reliable method for the reconstruction of small to mediumsized oroantral defects with minimum complications.